Sexual Orientation and Human Rights - Thomas, Laurence; Levin, Michael (Rowman & Littlefield Publishers, 2000)
What rights govern heterosexual and homosexual behaviors? Two distinguished philosophers debate this important issue in Sexual Orientation and Human Rights. Laurence Thomas argues that a society which has the constitutional resources to protect hate groups can protect homosexuals without valorizing the homosexual life-style. He defends the view that the Bible cannot warrant the venom that, in the name of religion, is often expressed against homosexuals. Michael Levin defends the unorthodox view that the aversion some people experience toward homosexuality deserves respect. He further argues that while homosexuals enjoy the same rights as others to be free of violence and discrimination, they do not have more extensive rights.